Islamic Republic of Afghanistan : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria, and Rephasing and Extension of the Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Islamic Republic of Afghanistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Fifth Review for Afghanistan under the Poverty Reduction and Growth Facility (PRGF). Performance under the PRGF-supported program has been mixed. Monetary and financial policies were broadly consistent with the program. However, difficulties were evident in reforming public enterprises and in the fiscal area. The economic program for 2009/10 envisages a prudent monetary policy to ensure fast disinflation, fiscal adjustment anchored on remedial measures to increase revenues and contain spending, and closer monitoring of public enterprises that pose fiscal risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet